KIR genes and their human leukocyte antigen ligands in the progression to cirrhosis in patients with chronic hepatitis C - Marangon, Amanda Vansan; Silva, Giovanni Faria [UNESP]; Verdichio de Moraes, Camila Fernanda [UNESP]; Tomasini Grotto, Rejane Maria [UNESP]; Pardini, Maria Ines de Moura Campos [UNESP]; de Pauli, Dayse Sousa; Sell, Ana Maria; Laguila Visentainer, Jeane Eliete; Moliterno, Ricardo Alberto (Elsevier B.V., 2011)
Natural killer (NK) cells play pivotal roles in immune responses against infection with viruses, such as hepatitis C virus (HCV), and killer cell immunoglobulin-like receptors (KIRs) are related to the activation and inhibition of NK cells. The aim of this study was to investigate the possibility that KIR genes and their human leukocyte antigen (HLA) ligands influence progression to cirrhosis in patients infected with genotype 1 of HCV. A total of 145 Brazilian patients with confirmed chronic hepatitis C grouped from F0 to F4 according to fibrosis progression to cirrhosis were evaluated. Genotyping of KIR and HLA genes was performed by polymerase chain reaction with sequence-specific oligonucleotide probes. The HLA-C2 KIR ligand was more frequent in patients than in healthy controls (74.5% vs 64.3%, p = 0.04, odds ratio (OR) = 1.6, 95% confidence interval (Cl) = 1.03-2.52). Moreover, the HLA-C1C2 genotype was more frequent in patients with advanced fibrosis or cirrhosis (F3-F4 group) than in patients in the F0-F2 group (61.6% vs 44.7%, p = 0.06) and in the F4 group compared with the F0-F3 group (65.7% vs 46.7%, p = 0.05, OR = 2.19, 95% CI = 1.01-4.73). NK and KIR ligands may contribute to the development of liver damage in patients chronically infected by HCV. (C) 2011 American Society for Histocompatibility and Immunogenetics. Published by Elsevier B.V. All rights reserved.
Keywords: NK cells; HLA; KIR; Hepatitis C; Liver fibrosis